PERTIMBANGAN iHAKIM iPADA iPENERAPAN iSAKSI iMAHKOTA TERHADAP iTINDAK iPIDANA iPEMBUNUHAN iBERENCANA i DENGAN iPENYERTAAN i i(Studi iPutusan iNomor i717/Pid.B/2015/PN.Tjk) - Gideon Moris E. P HAREFA (Jurnal Panah Hukum, 2023)
The icrown iwitness iis ia ico-defendant iwitness iwho ionly iexists ifor ithe icrime iof ipremeditated imurder iwith iinclusion, iwhich imeans ithat ithe icrown iwitness iis ionly iavailable ifor ithe iinclusion ioffense. iOne iapplication iof ithe icrown iwitness iin ithe icase iof ithe icrime iof ipremeditated imurder iwith iparticipation iand iwhich iwas iexamined iand itried iby ithe iTanjung iKarang iDistrict iCourt iis idecision iNumber i717/Pid.B/2015/PN.Tjk. iwhere iin ithis idecision, ithe ipanel iof ijudges iused ithe icrown iwitness ias ia iwitness iin ievidence iand ithe iperpetrator iwas isentenced ito ia iform iof iimprisonment ifor i15 iyears iin iprison ifor iallegedly iviolating iArticle i340 iof ithe iCriminal iCode iJo. iArticle i55 iparagraph i(1) i1st iof ithe iCriminal iCode. iThe itype iof iresearch iused iis inormative ilegal iresearch iwith istatutory iapproach, icase iapproach, icomparative iapproach iand ianalytical iapproach. iData icollection iwas icarried iout iusing isecondary idata iobtained ithrough ilibrary imaterials iconsisting iof iprimary ilegal imaterials iand isecondary ilegal imaterials. iThe idata ianalysis iused iis idescriptive iqualitative ianalysis ior iconclusions iare idrawn iusing ithe ideductive imethod. iBased ion ithe iresearch ifindings iand idiscussion, iit ican ibe iconcluded ithat ithe ijudge's iconsideration iin iusing ia icrown iwitness iin ithe icrime iof ipremeditated imurder iwith iparticipation i(study iof idecision inumber i717/Pid.B/2015/PN.Tjk) iis iunfair, iwhere ithe ijudge iuses ijudgment ibased ion ithe iJurisprudence iof ithe iCourt iRI iSupreme iCourt iNumber: i1986 iK/Pid/1989 idated iMarch i21, i1990 ithe ijudge ishould ihave iadjusted ihis iconsiderations ito ithe ilatest isupreme icourt idecision iwhich icorrected ithe imistake iin iusing icrown iwitnesses, inamely iMARI iJurisprudence, iNo. i1174 iK/Pid/1994 idated i3 iMay i1995, iMARI, iNo.1952 iK/Pid/1994, idated i29 iApril i1995, iMARI, iNo. i1950 iK/Pid/1995, idated i3 iMay i1995 iand iMARI, iNo. i1592 iK/Pid/1995, idated i3 iMay i1995. iIn ithis icase ithe iuse iof icrown iwitnesses iis isaid ito ibe icontrary ito ithe iCriminal iProcedure iCode iwhich iupholds ihuman irights. iThe iauthor isuggests ithat ithe iapplication iof ithis icrown iwitness iis iregulated iin ia ispecial ilaw, ior iPERMA, iSEMA iso ias inot ito icreate idifferent ilegal iunderstandings iregarding ithe iapplication iof icrown iwitnesses iand ithe irights iof ieach ivictim iand idefendant iare iprotected ibased ion ilegal iprovisions